Independencia funcional y logro de objetivos tras rehabilitación interdisciplinaria en pacientes con ataque cerebrovascular: evaluación con escalas FIM y GAS (2026)
Stroke constitutes one of the leading causes of disability worldwide and requires interdisciplinary rehabilitation processes that promote functional recovery and the reintegration of patients into their daily activities. In this context, the Functional Independence Measure (FIM) and the Goal Attainment Scaling (GAS) are widely used tools to quantify functional progress and the achievement of therapeutic goals. Objective: To describe changes in functional independence and goal attainment in patients with post-stroke sequelae following participation in the Interdisciplinary Rehabilitation Process (PIR®) of Clínica Universidad de La Sabana during the period 2023–2024.